STRUKTUR, PERILAKU, DAN KINERJA PASAR KOMODITAS JAGUNG DI KECAMATAN MADAPANGGA KABUPATEN BIMA - Muflihun, Sadiqin; Syafiuddin, Syafiuddin; Mardiyati, Sri; Natsir, Mohammad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Corn is an agricultural commodity that has an important role as food and feed. The demand for corn which continues to increase in line with the continued development of the food and feed industry indicates the large role of corn in the growth of the food crops subsector. This study aims to determine the structure, conduct, and performance of the corn commodity market in Madapangga District, Bima Regency. The technique of determining the sample using snowball sampling. The number of respondents included 5 corn farmers, 7 collectors, and 4 wholesalers. Data analysis techniques used quantitative descriptive analysis namely CR 4 (Concentration Ratio for The Bighest Four) analysis, Herfindahl Hirschman Index (HHI), marketing margins, farmer's share, Minimum Efficiency Scale (MES), and profit and cost ratios. The results showed that the corn commodity market structure at the farm level was perfect competition (CR4=16.77%, HHI=0.005), the collector trader level was oligopoly (CR4=62.99%, HHI=0.14), and the trader level was large is an oligopoly (CR4=65.67%, HHI=0.27). The corn commodity market has entry and exit barriers, with an MES value of 15 percent. Farmers' conduct in developing the market value of corn commodities focuses on increasing the productivity and quality of corn. Collector trader conduct concentrates on direct purchases by visiting farmers, while wholesalers prioritize the quality of corn commodities. The performance of the corn commodity market is determined by a marketing margin of IDR 250.00 per kilogram, farmer's share of farmers and traders respectively reaching 97.8 percent and 96.8 percent, while the value of the profit and cost ratio is 0.93.